PEMETAAN DAN ANALISA KONFLIK ANTARA MASYARAKAT DESA MENAMANG KIRI DAN PT SURYA HUTANI JAYA KABUPATEN KUTAI KARTANEGARA KALIMANTAN TIMUR - Gantika, Naldi (Universitas Ekasakti, 2020)
The urge for a peaceful and fair settlement of forestry conflicts also encourages business actors in the Indonesian forestry sector to develop conflict resolution mechanisms through dialogue and mediation processes through both mandatory (mandatory) and voluntary (voluntary) mechanisms. The commitment to apply the principle of FPIC (Free, Prior and Informed Consent) or free consent without coercion along its industrial supply chain (Supply Chain) has been declared by plantation companies under the banner of the APP (Asian Pulp and Paper) or Sinar Mas forestry (SMF) group and the APRIL group (Asia Pacific Resources International Limited). Not only that, the commitment to maintaining High Conservation Values ​​contained in the company's work area was also expressed by the two major groups of players in the plantation forest industry in Indonesia. This condition has created opportunities for improved access and relations between the conflicting parties. In East Kalimantan, Conflict Mapping and Analysis was carried out in Menamang Kiri Village, Muara Kaman District, Kutai Kertanegara Regency. In the spatial mapping analysis that was carried out, part of the village of Menamang Kiri was within the concession of PT Surya Hutani Jaya (PT SRH), a wood supplier to APP. Mapping and Conflict Analysis is focused on extracting information related to governance and land management by PT SRH and the people of Menamang Kiri Village, conflicts or potential conflicts that arise and the parties involved, the perceptions of each party related to differences in interests, and policy analysis.